2000
DOI: 10.1097/00000658-200007000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Lymphatic Anatomy for Sentinel Node Biopsy in Breast Cancer

Abstract: The lessons learned from this study provide a functional concept of the breast lymphatic system and its role in metastasis. Anatomical and clinical investigations from the past strongly support these views, as do recent sentinel node studies. Periareolar blue dye injection appears ideally suited to identify the principal (axillary) metastasis route in early breast cancer. Awareness of the targeting mechanism and inherent technical restrictions remain crucial to the ultimate success of sentinel node biopsy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
116
1
13

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(139 citation statements)
references
References 20 publications
9
116
1
13
Order By: Relevance
“…Despite the different injection protocols, the precise position of the vital dye injection may be immaterial given the embryology of breast lymphatic tissue; studies have shown that the lymphatics of breast parenchyma and those of its overlying skin and are connected by a common subareolar lymphatic plexus (Sappey's complex) 26 . The presence of this plexus supports the hypothesis that a mammary gland and its overlying skin share the same lymphatic channels to the draining sentinel node 16,27 .…”
Section: Sentinel Node Methodologysupporting
confidence: 71%
See 3 more Smart Citations
“…Despite the different injection protocols, the precise position of the vital dye injection may be immaterial given the embryology of breast lymphatic tissue; studies have shown that the lymphatics of breast parenchyma and those of its overlying skin and are connected by a common subareolar lymphatic plexus (Sappey's complex) 26 . The presence of this plexus supports the hypothesis that a mammary gland and its overlying skin share the same lymphatic channels to the draining sentinel node 16,27 .…”
Section: Sentinel Node Methodologysupporting
confidence: 71%
“…The uptake kinetics of each mapping agent are different, but the function of both is to localise the sentinel node. It is thought that nanocolloids become entrapped within the sentinel lymph nodes either through a function of their particulate size 13,14 (the larger hydrodynamic diameter of 50-100nm for colloid requires a transit time of usually more than 1 hour 15 ) or because of phagocytosis by leukocytes which migrate to and are retained within the draining lymph nodes 16 . These entrapment processes are unlikely to be mutually exclusive, and other mechanisms may also exist, but the end result is localisation of the nanocolloid within the sentinel nodes rather than its diffuse spread to secondary nodes.…”
Section: Sentinel Node Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…A peritumoural injection technique visualises IM lymph nodes in about 15 -30% of women, whereas subdermal or subareolar injection of isotope does not seem to identify IM nodes (Kett et al, 1993;Borgstein et al, 1997Borgstein et al, , 2000Roumen et al, 1999;Cserni and Szekeres, 2001;Shen et al, 2001;Tanis et al, 2001). The mammary gland and the overlying skin clearly show a common lymphatic pathway to the axilla and the same axillary sentinel node in most cases (Dupont et al, 2001), but they do not appear to both drain to the IM chain.…”
mentioning
confidence: 99%